265 The design of a virtual museum to address social disconnection and pain among individuals with chronic pain (IWCP). (April 2022) - Koebner, Ian; Pena, Jorge
Abstract : OBJECTIVES/GOALS: Engagement with art may reduce the social disconnection that accompanies chronic pain. Disaggregating specific from non-specific effects of arts-based programs is challenging. This study creates an experimental virtual museum to identify the separate and joint effects of art and social connection. METHODS/STUDY POPULATION: Two x two factorial experiment with repeated measures: (1) Artwork present condition is a virtual exhibition featuring paintings from the Google Arts & Culture collection; (2) Artwork absent condition is the same exhibition space but with the paintings removed; (3) Social connection condition asks participants to write about a situation in which they felt more socially connected to others; (4) Social disconnection conditions asks participants to write about a situation in which they felt more socially disconnected from others. Participants: (1) English language proficiency; (2) â‰¥18 years; (3) Chronic moderate to severe pain; (4) Lonely; (5) Has electronic device with internet connection. RESULTS/ANTICIPATED RESULTS: Participants will be recruited through a 3-month social media campaign conducted by StudyPages, a clinical trial recruitment and management platform. This study will evaluate the effects of virtual art exposure and social connectivity priming on pain and social disconnection reduction among lonely IWCP. Pre-intervention scores for pain intensity, pain unpleasantness, and perceived social disconnection will be compared to post-intervention scores. Secondary outcome measures include (a) Museum visit data (e.g., user movement, click, object interaction, open comments) and (b) perceptions about artwork. DISCUSSION/SIGNIFICANCE: Psychosocial support for IWCP may improve pain-related outcomes. This studys data will help to optimize virtual museum interventions and provides the first data we are aware of to evaluate the specific effects of art in virtual museum engagement to reduce pain and social disconnection among IWCP.